Problematika Pernikahan Siri di Bawah Umur Perspektif Maqashid Syariah - Rahmi, Nailur; Pelani, Herman (Jurnal AL-AHKAM, 2024)
The type of research is field research, using qualitative methods. The primary data sources are couples who enter into unregistered marriages under age and the families of these couples. The secondary data is the number of couples who have underage unregistered marriages. Data was collected by means of interviews and documents. Data analysis uses Miles and Huberman theory by collecting data, reducing data, presenting data as well as drawing conclusions and verifying data. The data validity guarantee technique uses data source triangulation.The results of the research show that the problem of underage serial marriages in Nagari Binjai, Tigo Nagari District, Pasaman Regency, there are various kinds of problems, namely: economic problems, religion and age maturity problems. These problems result in the separation of several couples on the grounds that they are not economically strong due to their youth, lack of religious understanding or their immature age at marriage. Judging from the perspective analysis of maqashid sharia, this still tends to be inconsistent, the 5 main elements of maqashid sharia are: protecting religion (hifdz ad-dtn), protecting the soul (hifdz an-nafs), protecting reason (hifdz al-aql), protecting offspring (hifdz an-nasl), and guarding wealth (hifdz al-mal).